Resettlement, Resistance, and Coastal Niches on the Chukchi Peninsula - Holzlehner, Tobias (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2021)
As were other regions of Russia’s North, Chukotka (Chukotskii avtonomnyi okrug) was subjected to dramatic changes during the last century. Among the major long-lasting impacts for the Chukchi and Siberian Yupik Indigenous populations was a state-implemented village relocation policy that deemed dozens of historic settlements “unprofitable”, thus subject to forced closure and resettlement. Traumatic loss of homeland, the curbing of native patterns of (maritime) mobility, and the vanishing of traditional socioeconomic structures sent devastating ripples through the fabric of Indigenous communities, with disastrous results on societal health. To explore the intricate relationships between state-enforced resettlement and landscape interaction, particularly the perception and utilization of the environment, it is critical to look closely at Chukotka’s coastal environment. The article argues that the unique coastal landscape of Chukotka has influenced—while mitigating—the effects of the forced relocations. Improvised design and the reclaiming of formerly closed settlement sites play a paramount role here, with the reoccupation of old settlement niches representing a reconnection with a lost relationship to the littoral environment. The contemporary inhabitation and utilization of formerly closed villages show how the coastal landscape represents not only a “reservoir” in an ecological sense, but also a littoral reserve by providing the space for alternatives outside the congregated communities. Displacement destroys the sense of community, but in a reverse logic, a sense of community can also be established through renewed emplacement. The creation of autonomous social spaces is therefore part of an ongoing spatial resistance that actively uses the ecological niches of a coastal landscape to counter the long-lasting and detrimental effects of state-enforced resettlement policies.